Газофазне сольвато-стимульоване адсорбційне модифікування нанорозмірного кремнезему нелеткими органічними сполуками - Voronin, E. F.; Nosach, L. V.; Gun'ko, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2010)
An effective method of adsorption modifying of nanosilica with non-volatile organic compouds in the gaseous dispersion medium has been developed. It is based on stimulated migration of organic molecules from the condensed state into adsorbed one on the surface. This process is conditioned by strong molecular interactions between surface and molecule and weekening of interactions between molecules of the modifier caused by their solvation (solvation stimulation).